2006
DOI: 10.1086/508352
|View full text |Cite
|
Sign up to set email alerts
|

Ritonavir-Boosted Tipranavir Demonstrates Superior Efficacy to Ritonavir-Boosted Protease Inhibitors in Treatment-Experienced HIV-Infected Patients: 24-Week Results of the RESIST-2 Trial

Abstract: TPV/r had superior antiviral activity and increased immunologic benefits, compared with CPI/r, at week 24 among treatment-experienced patients infected with multidrug-resistant HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 25 publications
3
72
0
Order By: Relevance
“…In our patients, in fact, OBS was an independent predictor of VR by both multivariate linear and logistic regression analyses. Moreover, subjects with two or more active drugs in the OB regimen were more likely to achieve a VR than those with less active drugs, confirming the possible OBS cutoff suggested previously (3,6,8).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In our patients, in fact, OBS was an independent predictor of VR by both multivariate linear and logistic regression analyses. Moreover, subjects with two or more active drugs in the OB regimen were more likely to achieve a VR than those with less active drugs, confirming the possible OBS cutoff suggested previously (3,6,8).…”
Section: Discussionsupporting
confidence: 80%
“…In the RESIST-1 and the RESIST-2 studies, the efficacy and safety of TPV-RTV (500 mg/200 mg twice daily) in 1,509 highly treatment-experienced HIV-1-positive patients were assessed. Analysis at 48 weeks showed that the TPV-RTV-containing regimens significantly improved the immune and virological responses (VRs) compared to the responses to an RTV-boosted comparator PI plus an optimized background (OB) regimen (3,6,8).Different factors have been found to be associated with the virological and immunological responses: a lower viral load (VL) at the baseline, the use of enfuvirtide (T20) as a part of the OB regimen, the presence of two or more active drugs in the OB regimen (OB score [OBS], Ն2) (3,6,8), and the baseline numbers of specific TPV-associated resistance mutations (TPV RMs) (2). Moreover, the TPV trough concentration (C trough ) and phenotypic inhibitory quotient (IQ) have also been shown to be associated with the VR at week 24 (12a, 16).…”
mentioning
confidence: 99%
See 3 more Smart Citations